Dynamically resolved self-assembly of S-layer proteins on solid surfaces - Stel, Bart (2018)
By using high-speed and high-resolution Atomic Force Microscopy (AFM), it was possible to resolve within a single experiment the kinetic pathway in S-layer self-assembly at the solid-liquid interface, obtaining a model that accounts for the nucleation, growth and structural rearrangements in 2D protein self assembly across time (second to hours) and spatial scales (nm to microns).